Proceedings of 2012 3rd International Asia Conference on industrial engineering and management innovation (IEMI2012) - Dou, Runliang (Springer Berlin Heidelberg, 2013)
The purpose of the 2012 3rd International Asia Conference on Industrial Engineering and Management Innovation (IEMI2012) is to bring together researchers, engineers and practitioners interested in the application of informatics to usher in new advances in the industrial engineering and management fields.